An mHealth Approach to Extend a Brief Intervention for Adolescent Alcohol Use and Suicidal Behavior: Qualitative Analyses of Adolescent and Parent Feedback. Issue 4 (2nd October 2019) - O'Brien, Kimberly H. McManama; Wyman Battalen, Adeline; Sellers, Christina M.; Spirito, Anthony; Yen, Shirley; Maneta, Eleni; Ryan, Colleen A.; Braciszewski, Jordan M.
Abstract: Mobile health (mHealth) tools that supplement inpatient psychiatric care can maintain and enhance intervention effects following hospitalization. Adolescents hospitalized following a suicidal event represent a vulnerable population who could greatly benefit from such an mHealth intervention. In specific, suicidal adolescents who drink alcohol are in need of robust interventions that address the bidirectional relationship between alcohol use and suicidal thoughts and behaviors, because it puts them at especially high risk for suicide upon discharge. The purpose of this study was to conduct qualitative interviews to gather feedback to improve a brief alcohol intervention provided to suicidal adolescents during psychiatric hospitalization, and to develop a mHealth tool to extend care after discharge. Participants, eight adolescents and their parents, identified the need for a smartphone application to deliver intervention content to adolescents and parents during the posthospitalization period. Adolescents sought support in meeting alcohol- and mood-related goals, while parents desired general resources as well as tips for conversations with their adolescent about mood and alcohol use.